Children and pollution : why scientists disagree - Moore, Colleen F., 1950- (Oxford University Press, 2009)
How does pollution impact our daily quality of life? What are the effects of pollution on children's development? Why do industry and environmental experts disagree about what levels of pollutants are safe? In this clearly written book, Moore traces the debates around five key pollutants--lead, mercury, noise, pesticides, and dioxins and PCBs--and provides an overview of the history of each pollutant, basic research findings, and the scientific and regulatory controversies surrounding it. Moore focuses, in particular, on the impact of these pollutants on children's psychological development-